Effects of 12-week in-season low-intensity plyometric training on dynamic balance of pre-pubertal female volleyball players - Elif Turgut; Filiz Fatma Colakoglu; Pınar Serbes; Cengiz Akarcesme; Gul Baltacı (Türk Spor ve Egzersiz Dergisi)
Investigating the effects of plyometric training on dynamic balance of prepubertal female volleyball players may enable to enhance comprehensive knowledge about neuromuscular control enhancement and may further provide basis for developing training protocols encouraging lifelong regular physical activity for prepubertal volleyball players. The aim of this study was to compare the effects of 12-week plyometric training on dynamic balance in female prepubertal volleyball players. Twenty-nine female volleyball players were recruited to participate in the study. Participants were randomly separated into two study groups; plyometric training (n=14) and control group (n=15). All participants were assessed at baseline and after 12-week training. Dynamic balance was assessed with Star Excursion Balance test (SEBT). A repeated-measures ANOVA was performed. Comparisons showed that after 12-week training, plyometric training resulted in improvements in SEBT anterior, posterolateral and posteromedial scores for both dominant and nondominant leg whereas there were no differences found in the control group. Compared to control training, plyometric training resulted in additional gains for dynamic balance in female prepubertal volleyball players. The findings of the study provide basis for developing training protocols for prepubertal volleyball players.